The prevalence and demographic features of congenital cytomegalovirus infection in an urban area of East Asia: A population-based study. - Tzong-Hann Yang; Hung-Meng Huang; Wei-Chung Hsu; Po-Nien Tsao; Tien-Chen Liu; Chuan-Jen Hsu; Li-Min Huang; Chuan-Song Wu; Shih-Ming Weng; Chun-Yi Lu; Chen-Chi Wu (PLoS ONE)
Congenital cytomegalovirus (cCMV) infection is the leading environmental cause of childhood hearing impairment. However, its significance remains largely undocumented in many regions of the world. The purpose of this study was to investigate the prevalence and clinical features of cCMV infection in East Asia. Neonates born at a municipal hospital in Taipei were prospectively recruited and underwent concurrent hearing and CMV screenings. Those who failed the hearing screening or screened positive for CMV were subjected to a focused audiological and/or virological surveillance. The characteristics of the newborns and their mothers were compared between the CMV-positive and CMV-negative groups. Of the 1,532 newborns who underwent concurrent hearing and CMV screenings, seven (0.46%) were positive for cCMV infection. All seven CMV-positive newborns were asymptomatic at birth, and none of them developed hearing or other symptoms during a follow-up period of 14.4±6.3 months. The mothers of the CMV-positive newborns demonstrated higher gravidity (2.4 ± 1.4 vs. 2.1 ± 1.2) and parity (2.0 ± 1.2 vs. 1.6 ± 0.7) than those in the CMV-negative group; however, the difference did not reach statistical significance. The prevalence of cCMV infection in Taipei newborns was 0.46%, which is slightly lower than that of other populations and that of a previous report in the Taiwanese population. The relatively low prevalence in this study might be attributed to the improved public health system and decreased fertility rate in Taiwan.